Territorial – Means a Spatial, or a New Approach to the Old Criminological Problem Solving - Bakharev, Dmitry V. (International Journal of Criminology and Sociology, 2019)
The article presents a new approach to the possibilities of using the method of analysis of patterns of territorial differences formation in crime rates in regions of the same country in order to expand the understanding of crime causative complex as a whole. The author proves that the effectiveness of territorial approach to crime causes understanding will reach its greatest extent when it is a criminological analysis of territorial-spacial systems functioning, a revelation of their destabilizing factors, sources of disorganization and social tension. But this requires a preliminary solution to the problem of identifying the patterns of territorial socio-economic systems functioning, that the author proposes to do on the basis of the "New Economic Geography" modern achievements. For such an approach, the name "spatial analysis of causative crime complex" is claimed. This analysis, carried with reference to some regions of Central Federal District of Russia, demonstrated the received results importance for a better mechanism of theoretical understanding of crime existence in society. In particular, the conclusion was made that the main reason of crime rates increasing within the territorial socio-economic system (specifically, the Russian Federation region) is the imbalance between theoretically estimated potential of socio-economic development of a definite region at a certain stage of society development and actual vector and dynamics of such development in reality.